Interpublic Public Group - Agarwal, Suravi (ATLAS SkillTech University, 2024)
I had the privilege of serving as an Accounting Intern at IPG Media Group for a duration of two months. During my internship, I was exposed to a diverse range of accounting tasks and responsibilities, gaining valuable hands-on experience in a dynamic and professional corporate environment. This executive summary provides an overview of my daily tasks, responsibilities, and the skills I developed during my time at IPG Media Group. Daily Tasks and Responsibilities.
Project Report on Interpublic Public Group (2022-2024) Under the Guidance of Prof. Ameya Ambulkar
Keywords: IPG; Accounting